Effect of Grafting Height on Success and Subsequent Growth of Acid Lime (Citrus aurantifolia Swingle) Saplings - Chalise, B; Paudyal, KP; Srivastava, SP (Nepal Journal of Science and Technology, 2014)
A field experiment was conducted at National Citrus Research Program (NCRP), Paripatle, Dhankuta to determine the best grafting height for the highest success of grafting and the maximum growth of saplings during 1st January to 30th December, 2010. Scions were collected from the mother plant ‘NCRP-49’ grown under screen house and grafted onto one-year-old trifoliate orange seedling rootstocks by shoot-tip method at 4 cm, 8 cm, 12 cm, 16 cm and 20 cm height from the collar region as the treatment. The grafts were planted inside the closed tunnel made from bamboo splits, jute and plastic sheet at 10×8 cm spacing in 64×100 cm experimental plots laid out in randomized complete block design (RCBD) with four replications containing 80 grafts per plot. Treatments were allotted on the experimental plots randomly. The success of grafting was not affected by the height of grafting, however, growth of sapling was found significantly affected by the height of grafting. Observation taken on saplings after one year of grafting revealed that the maximum scion height (42.13 cm), the highest number of leaves per sapling (47.50), the highest growth of scion diameter (55.61%), maximum length of primary branches (31.19 cm), maximum number of secondary branches per sapling ((3.24), the highest length of secondary branches (11.59 cm), the highest canopy volume (15440 cm3) and the highest graft spread (24.35 cm) were found on the sapling grafted at 16 cm height of the trifoliate orange rootstock. Hence, from the study it is concluded that the most suitable height of grafting acid lime on trifoliate orange rootstock was 16 cm. DOI: http://dx.doi.org/10.3126/njst.v14i2.10412 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 25-32